1987
DOI: 10.1063/1.98173
|View full text |Cite
|
Sign up to set email alerts
|

Carrier lifetime versus ion-implantation dose in silicon on sapphire

Abstract: We have measured the dependence of the free-carrier lifetime on 0 + ion-implantation dose in silicon-on-sapphire. At low implant doses, the carrier trapping rate increased linearly with the trap density introduced by ion implantation. At doses above 3 X 10 J4 cm-2 the measured carrier lifetime reached a limit of 600 fs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(80 citation statements)
references
References 11 publications
5
74
1
Order By: Relevance
“…Studies have shown that the recombination time in unpassivated Si is of the same order as the transition time from transient to steady state behavior reported here. 12,13 If indeed the electrons recombine after ~100 ps, then the steady state component should be driven solely by the diffusion of heat (thermal wave). To verify this assertion a second experiment was conducted that involved coating the sample with a thin (30 nm) aluminum film.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the recombination time in unpassivated Si is of the same order as the transition time from transient to steady state behavior reported here. 12,13 If indeed the electrons recombine after ~100 ps, then the steady state component should be driven solely by the diffusion of heat (thermal wave). To verify this assertion a second experiment was conducted that involved coating the sample with a thin (30 nm) aluminum film.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found in [35] that free-carrier trapping rate in this material increases linearly with O + -ion implantation dose and the measured carrier lifetime decreases down to the limit of 600 fs at doses above 3·10 14 cm -2 . Fig.…”
Section: Radiation-damaged Silicon-on-sapphirementioning
confidence: 99%
“…6 shows the carrier lifetime in SOS as a function of the implanted O + -ion dose. As a most probable cause of this carrier lifetime limit, the authors of [35] pointed out the amorphisation of the crystalline silicon and the saturation of the trap density. Similar conclusion was made in [36], where transient carrier dynamics in the radiation-damaged SOS was measured by the optical pump-THz probe technique.…”
Section: Radiation-damaged Silicon-on-sapphirementioning
confidence: 99%
“…During operation, the excitation pulses short the transmission line by producing carriers in the silicon. These carriers are trapped in less than 600 fs [14]. This transient shorting of the line produces two approximately 0.5-ps electrical pulses which propagate as single-mode excitations in opposite directions down the transmission line.…”
Section: Generation Of Single-mode Ultrashort Electrical Pulses Omentioning
confidence: 99%